The use of English as instructional language in English language teaching at senior high school level in Jayapura - Komari Komari; Rosi F Sumedi; Upi Laila Hanum; Emon Paranoan (Journal of English Language Proficiency, 2026)
The use of English as the instructional language in English Language Teaching (ELT) is widely acknowledged as a key factor in enhancing learners’ communicative competence. In many English as a Foreign Language (EFL) contexts, however, teachers tend to rely heavily on the first language (L1), which may limit students’ exposure to the target language (L2). This study investigates the proportion of English used as instructional language in senior high schools in Jayapura and examines its impact on students’ English proficiency, particularly in listening and speaking skills. A descriptive quantitative design was employed involving 22 English teachers from 21 senior high schools. Data were collected through classroom observations, questionnaires, and documentation of students’ academic performance. The findings reveal that the average use of English as instructional language is relatively low (39%), while Indonesian dominates classroom interaction (61%). English is mainly used during opening and closing sessions, whereas Indonesian is predominantly used during core instructional activities. Statistical analysis indicates that the use of English does not significantly affect students’ overall academic achievement (M = 61%, SD = 18.2), but it has a substantial impact on students’ listening and speaking competence (M = 31%, SD = 15.6). Schools with higher exposure to English demonstrate better oral proficiency outcomes. These findings highlight the importance of increasing meaningful exposure to English in EFL classrooms. It is recommended that teachers adopt a balanced approach by maximizing L2 use while employing L1 strategically to facilitate comprehension.